Intra‐Arterial Thrombolysis After Mechanical Thrombectomy in Patients with Acute Ischemic Stroke: A Systematic Review and Meta‐Analysis With Trial Sequential Analysis - Tallal Mushtaq Hashmi; Mushood Ahmed; Hadiah Ashraf; Raheel Ahmed; Faizan Ahmed; Majid Toseef Aized; Gregg C. Fonarow (Stroke: Vascular and Interventional Neurology)
Background The potential role of adjunctive intra‐arterial thrombolysis (IAT) in improving outcomes following mechanical thrombectomy (MT) remains unclear. This meta‐analysis evaluates the efficacy and safety of IAT after MT compared to MT alone in patients with acute ischemic stroke. Methods We searched PubMed, Embase, and the Cochrane Library from inception to January 2025 with no language restrictions. Additionally, grey literature sources were explored. Randomized controlled trials comparing IAT after MT versus MT alone in acute ischemic stroke were included. Odds ratios (ORs) with 95% CIs were pooled using a random‐effects model in R. Trial sequential analysis was performed for the primary favorable outcomes assuming a 30% relative risk increase, an alpha level of 5%, and 80% power. The primary outcome was excellent functional outcome (modified Rankin Scale score 0–1 at 90 days); secondary outcomes included good functional outcome (modified Rankin Scale score 0–2), symptomatic and any intracranial hemorrhage, and severe adverse events. Results Four randomized controlled trials encompassing 1395 patients (MT and IAT: 701; MT alone: 694) met the inclusion criteria. The pooled analysis demonstrated significantly improved excellent functional outcome (OR, 1.31 [95% CI, 1.06–1.63]) in patients receiving IAT after MT compared with MT alone. No statistically significant difference was observed for good functional outcome (OR, 1.07 [95% CI, 0.86–1.32]), all‐cause death (OR, 0.92 [95% CI 0.70–1.21]), symptomatic intracranial hemorrhage (OR, 1.31 [95% CI, 0.74–2.34]), any intracranial hemorrhage (OR, 1.30 [95% CI, 0.96–1.76]), and severe adverse events (OR, 1.05 [95% CI, 0.67–1.66]). Trial sequential analysis revealed sufficient evidence to confirm a 30% relative risk increase for excellent functional outcome. The overall quality of evidence was moderate except for good functional outcome, rated as low. Conclusion IAT following MT was associated with increased odds of excellent functional outcomes at 90 days compared with MT alone, with no significant differences observed in intracranial hemorrhage, all‐cause mortality, or severe adverse events.